ASPEK YURIDIS KEPEMILIKAN KONDOTEL SWISS BELHOTEL TUBAN – KUTA BALI OLEH WARGA NEGARA ASING BERDASARKAN PP NO. 103 TAHUN 2015 - Nastasha Estherina. G; Anda Setiawati (Reformasi Hukum Trisakti, 2021)
If previously the apartments were only meant for domestic use, they are now also utilized for non-residential uses, such as service hotels, one of which is situated in Bali, namely the Swiss Belhotel Tuban - Kuta Bali Condotel, whose existence draws tourists from abroad. According to PP No. 103 of 2015 concerning Ownership of Residential or Residential Houses by Foreigners Domiciled in Indonesia, the foreigner must be domiciled in Indonesia, provide economic benefits and the condotel purchased must be a new unit and built on Land Right to Use in order to be able to own and control the Swiss Belhotel Tuban - Kuta Bali Condotel unit. Simply said, there is a violation in the condotel unit's ownership Condotel ownership is given with a "strata title certificate" that includes 14 units that are owned and controlled by foreigners, in accordance with the provisions of PP No. 103/2015 and UURS. Given that the condotel is constructed on land with usage rights, foreigners should have ownership rights over flat units (HMSRS) rather than a "strata title" for their unit.